Rheological Behavior of Aqueous Suspensions of Highly-Refine Pulp Fibres (Annual Transactions of the Nordic Rheology Society, 2025)
This study focuses on the rheological properties of highly-refined pulp fibres (HRF) as a potential alternative to energy-intensive microfibrillated and nanofibrillated celluloses (MFC/NFC). HRF, produced via conventional refining, has a broad size distribution but may offer similar functional benefits. We performed a detailed rheological analysis of HRF suspensions at four refining levels and five solids contents (1.2–3.0 wt%), using amplitude and frequency sweep measurements to assess viscoelastic properties, and steady-state viscosity measurements to examine flow behaviour.